Revisiting Kadenbach: Electron flux rate through cytochrome c‐oxidase determines the ATP‐inhibitory effect and subsequent production of ROS. (12th May 2016) - Vogt, Sebastian; Rhiel, Annika; Weber, Petra; Ramzan, Rabia
Abstract : Mitochondrial respiration is the predominant source of ATP. Excessive rates of electron transport cause a higher production of harmful reactive oxygen species (ROS). There are two regulatory mechanisms known. The first, according to Mitchel, is dependent on the mitochondrial membrane potential that drives ATP synthase for ATP production, and the second, the Kadenbach mechanism, is focussed on the binding of ATP to Cytochrome c Oxidase (CytOx) at high ATP/ADP ratios, which results in an allosteric conformational change to CytOx, causing inhibition. In times of stress, ATP‐dependent inhibition is switched off and the activity of CytOx is exclusively determined by the membrane potential, leading to an increase in ROS production. The second mechanism for respiratory control depends on the quantity of electron transfer to the Heme aa3 of CytOx. When ATP is bound to CytOx the enzyme is inhibited, and ROS formation is decreased, although the mitochondrial membrane potential is increased. Abstract : ATP‐binding inhibits Cytochrome c Oxidase, and ROS formation is decreased. This mechanism depends on the quantity of electron transfer to the Heme aa3 of CytOx. In times of stress, ATP‐dependent inhibition is switched off and activity of CytOx is exclusively determined by the membrane potential, leading to increased ROS production.